A Research and Critical Review of the Mystical Ideas of Syed Ali Hajveri and Allama Muhammad Iqbal - Ali, Mian Sajid; Javed, Tariq (sourcecoder, 2024)
This research examines the Sufism of Ali Hajveri and Allama Iqbal. In this research, it has been seen that what kind of ideas did Ali Hajveri and Iqbal have about Sufism? Ali Hajveri was a well-known Sufi, preacher and theologian of the eleventh century AD. He played an important role in the spread of Islam in South Asia. Sufism was losing its original status during his time. In these circumstances, the great achievement of Ali Hajveri is that through his teachings, he explained the true meanings and concepts of Sufism to the people and created enlightenment within them. Iqbal was born in 1877, almost eight hundred years after Ali Hajveri. Even during the time of Iqbal, many myths were created in Sufism. Iqbal opposed Sufism that makes man lazy and indolent and emphasized Sufism that makes man active. It is as if both of them presented the correct teachings of Sufism to the people in their respective times. For this reason, this topic was chosen for a detailed review of the mystic ideas of both. Although this is a narrative research, but since it also requires a comparative study of the views of two people, the principles of comparative research are also used in it. The research has come to the conclusion that the mystic ideas of Hajweri and Iqbal are more or less the same.